Determining the Effectiveness of Play Therapy in Aggression in Children with Oppositional Disobedience Disorder - Rafiei Bandari, Vahid; Kamali, Esmat; Mohamadizadeh, Fatemeh (Iranian Journal of Neurodevelopmental Disorders, 2023)
Background and Purpose: One of the prominent features of disobedience disorder is coping with aggression, aggression and hyperactivity. These children are very aggressive in their communication behaviors with parents and others and are constantly attacked; therefore, the aim of this study was to determine the effectiveness of play therapy in aggression in children with oppositional disobedience disorder.Method: The present study was a quasi-experimental pretest-posttest with a control group. The statistical population was all the children in the second grade of elementary school with confrontational disobedience in the education and training district of Bandar Abbas in the academic year of 2022-2023, 30 people were selected by convenience sampling method and randomly divided into two experimental groups. And witnesses were placed (15 people in each group). Data collection tools included the Gado and Sprafkin (2002) Parental Symptoms Questionnaire and the Aachenbach (1991) Behavioral Inventory. The experimental group underwent 8 sessions of 60 minutes of play therapy therapy Nell (2015) by the researcher, but the control group did not receive any training, after the training was retested. For statistical analysis of data, mean, standard deviation and univariate analysis of covariance were used with SPSS software version 22 at the significance level of α = 0.05. Findings: The results showed that in the post-test after adjusting the post-test scores on the pre-test scores, the mean aggression scores of the experimental group compared to the control group decreased significantly (p